Potensi Ekstrak Kulit Nanas (Ananas comosus) Sebagai Antimikroba - Sinaga, Herman Fransiskus; Apriliana, Ety; Septiani, Linda; Kurniati, Intanri (CV. Jasa Sukses Abadi, 2025)
Pineapple is one of the traditional plants that may be used as an alternative treatment to reduce pathogenic microbes. Its content is rich in chlorine, iodine, phenol and the enzyme bromelain which functions to stop microbial growth. This research aims to determine the potential of pineapple peel extract (Ananas comosus) as antimicrobe agents. This research uses a literature review study method, namely by using research articles obtained through a literature search process related to the potential use of pineapple peel extract on microbe from 2015 to 2025. Pineapple peel extract contains the main compounds, namely flavonoids, polyphenols, bromelain and saponins. This content causes pineapple skin extract (Ananas comosus) to have an effect on microbes.